Electrically pumped continuous‐wave 1.3‐µm InAs/GaAs quantum dot lasers monolithically grown on Si substrates. Issue 2 (1st April 2014) - Wu, Jiang; Lee, Andrew; Jiang, Qi; Tang, Mingchu; Seeds, Alwyn J.; Liu, Huiyun
Abstract : Continuous‐wave (CW) operation of InAs/GaAs quantum dot (QD) lasers monolithically grown on Si substrates by molecular beam epitaxy is presented. The peak lasing wavelength of 1278 nm is accompanied by a low threshold current density of 458 A/cm 2 at 8°C using a GaAs buffer layer directly grown on the Si substrates. The improvement in laser performance is due to improved crystal quality of the GaAs buffer layer. The demonstration of a CW QD laser also benefits from using top–top contacts, which route the current through the laser active layer to avoid the high‐density defects near the Si/GaAs interface. These results demonstrate the growing potential of the monolithically integrated III–V QD lasers on the Si substrates.